Analisis Pengaruh Keterikatan Kerja, Iklim Organisasi dan Kepuasan Kerja Terhadap Kinerja Karyawan PT XYZ - Michelle, Michelle; Rostiana, Rostiana (Jurnal Manajemen Bisnis dan Kewirausahaan, 2020)
This study aims to explain the role of work engagement, organizational climate, and job satisfaction on employee performance at PT XYZ. This research is a causality research conducted by cross sectional method. The sampling technique is done by convenience sampling. Data collection was carried out using a questionnaire instrument which was then analyzed using multiple linear regression analysis. The results of the study explained that work engagement, job satisfaction, and organizational climate play a positive role on the performance of employees at PT XYZ. These results explain that more employees feel they have a good attachment to the company, have satisfaction with the work done, and feel a conducive organizational climate that can support employees at PT XYZ to show better performance.